Rebuilding trust in local governance in conflict-affected settings - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
With the participation of over 40 attendees from government institutions, the private sector, research institutes and educational institute, the long-anticipated half-day seminar titled "Rebuilding Trust in Local Governance in Conflict-Affected Settings" took place on June 26, 2025, at the ILRI Campus in Addis Ababa, Ethiopia. The event was co-organized by IFPRI, IGC, CGIAR-Policy Initiative, and CGIAR-FSS programs. The seminar commenced with opening remarks from Alemayehu Seyoum Taffesse of IFPRI-Ethiopia and Tewodros Gebrewolde of IGC. An engaging discussions were made between the participants following the presentation on "Rebuilding Trust in Local Leadership in Conflict-affected Settings: The Impact of Community-based Cash Transfers" by Alemayehu Seyoum Taffesse and on "Participatory Targeting of Community-based Cash transfers for Rebuilding Trust in Local Governance in Conflict-Affected Settings" by Halefom Nigus.